Oxygen-releasing biomaterials for chronic wounds breathing: From theoretical mechanism to application prospect - Yu He; Qiang Chang; Feng Lu (Materials Today Bio, 2023)
Chronic wounds have always been considered as “gordian knots” in medicine, in which hypoxia plays a key role in blocking healing. To address this challenge, although tissue reoxygenation therapy based on hyperbaric oxygen therapy (HBOT) has been performed clinically for several years, the bench to bedside still urges the evolution of oxygen-loading and -releasing strategies with explicit benefits and consistent outcome. The combination of various oxygen carriers with biomaterials has gained momentum as an emerging therapeutic strategy in this field, exhibiting considerable application potential. This review gives an overview of the essential relationship between hypoxia and delayed wound healing. Further, detailed characteristics, preparation methods and applications of various oxygen-releasing biomaterials (ORBMs) will be elaborated, including hemoglobin, perfluorocarbon, peroxide, and oxygen-generating microorganisms, those biomaterials are applied to load, release or generate a vast of oxygen to relieve the hypoxemia and bring the subsequent cascade effect. The pioneering papers regarding to the ORBMs practice are presented and trends toward hybrid and more precise manipulation are summarized.